ROLE OF TRADITIONAL PRODUCTS IN DEVELOPMENT OF AGRITOURISTIC SERVICES (ON THE EXAMPLE OF PODKARPACKIE PROVINCE) - Kuźniar, Wiesława (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents the essence, scope and opportunities of development of regional traditional products in agritouristic households in the region of Podkarpacie. Apart from theoretical considerations, there were presented results of survey studies conducted in 2009 among 12 manufacturers of regional traditional products as well as among 300 prospective tourists. Development of traditional products, by exhibiting unique traditions and local cuisine customs, makes the offer of food services in tourism more attractive. However, the role of traditional products in agritouristic services development of Podkarpackie Province is still weak. The studies among the manufacturers indicate that in the nearest future, development of traditional products market will be closely connected with development of agritouristic services. It was also partially confirmed by prospective tourists.